Risk Factors, Site and Outcome of Intracranial Hemorrhage in Young Adults - Salma Haji, Salma Haji; Munir Afzal, Munir Afzal (Journal of Liaquat University of Medical & Health Sciences, 2024)
Objective: To determine risk factors and the site and outcome of intracranial Hemorrhage in young adults. Methodology: This cross-sectional observational study was conducted in neuromedicine ward 28 at Jinnah Postgraduate Medical center, Karachi, from September 2020 to August 2023. All emergency patients with evidence of Neuroimaging and symptomatic intracranial Hemorrhage were included. Using the Glasgow outcome scale, we investigated the risk factors, cause, location and prognosis of intracranial hemorrhage. Traumatic hemorrhages, primary sub-arachnoid hemorrhage and brain tumors were excluded. Results: 72 patients aged 16 to 40 years were included. Forty were Male patients, 55%, and 32 were female patients, 45%. The risk factors for intracranial hemorrhages were hypertension 60/72 (83.33%), ArterioVenous malformation 7/ 72 (9.33%), Cryptogenic 2/72 (2.77%), drug-induced 1/72 (1.38%), hypocholesterolemia 1/72(1.38%) and tobacco and alcohol intake 1/72 (1.38%). In 36/72 (50%), the location was basal ganglia, 25/72(34.72%) was in lobar, 7/72 (9.72%) in Subarachnoid, and 4/72 (5.55%) in other locations. The outcome was favorable in 65/72 (90.27%) patients. Conclusion: It has been found that hypertension, even in adults, is the leading risk factor for intracranial Hemorrhage below 40 years of age. Intracranial Hemorrhage is primarily present in the basal ganglia. AV malformation is the second most common risk factor in adults at our setup, and the outcome is good in adults. Drug, smoking, and hypocholesterolemia are less common causes of intracranial Hemorrhage in young adults.